МАНИПУЛЯТИВНАЯ КАРТИНА СОВРЕМЕННОЙ РЕКЛАМЫ: ЛИНГВИСТИЧЕСКИЙ АСПЕКТ - Зирка, Вера (Studia Rossica Posnaniensia, 2008)
The author analyzes the ways of the language manipulation used in Russian advertising texts. The analysis shows that the basis for the manipulation is constituted by word play consisting in the usage of the lexemes or lexeme groups of particular connotations or existing in non-conventional collocations. Native words connections with the English words or morphoelements are an important manipulative component.